The Effect of Gentamicin-Induced Readthrough on a Novel Premature Termination Codon of CD18 Leukocyte Adhesion Deficiency Patients - Simon, Amos J. (Public Library of Science, 2010)
BACKGROUND: Leukocyte adhesion deficiency 1 (LAD1) is an inherited disorder of neutrophil function. Nonsense mutations in the affected CD18 (ITB2) gene have rarely been described. In other genes containing such mutations, treatments with aminoglycoside types of antibiotics (e.g., gentamicin) were reported to partially correct the premature protein termination, by induction of readthrough mechanism. METHODOLOGY/PRINCIPAL FINDINGS: Genetic analysis was performed on 2 LAD1 patients. Expression, functional and immunofluorescence assays of CD18 in the patients were used to determine the in-vivo and in-vitro effects of gentamicin-induced readthrough. A theoretical modeling of the corrected CD18 protein was developed to predict the protein function. RESULTS: We found a novel premature termination codon, C562T (R188X), in exon 6 of the CD18 gene that caused a severe LAD1 phenotype in two unrelated Palestinian children. In-vivo studies on these patients' cells after gentamicin treatment showed abnormal adhesion and chemotactic functions, while in-vitro studies showed mislocalization of the corrected protein to the cytoplasm and not to the cell surface. A theoretical modeling of the corrected CD18 protein suggested that the replacement of the wild type arginine by gentamicin induced tryptophan at the position of the nonsense mutation, although enabled the expression of the entire CD18 protein, this was not sufficient to stabilize the CD18/11 heterodimer at the cell surface. CONCLUSION: A novel nonsense mutation in the CD18 gene causing a complete absence of CD18 protein and severe LAD1 clinical phenotype is reported. Both in vivo and in vitro treatments with gentamicin resulted in the expression of a corrected full-length dysfunctional or mislocalized CD18 protein. However, while the use of gentamicin increased the expression of CD18, it did not improve leukocyte adhesion and chemotaxis. Moreover, the integrity of the CD18/CD11 complex at the cell surface was impaired, due to abnormal CD18 protein and possibly lack of CD11a expression.